Auxological and endocrine phenotype in a population-based cohort of patients with PROP1 gene defects - Lebl, Jan; Vosáhlo, Jan; Pfaeffle, Roland W; Stobbe, Heike; Cerná, Jana; Novotná, Dana; Zapletalová, Jirina; Kalvachová, Bozena; Hána, Václav; Weiss, Vladimír; Blum, Werner F (European journal of endocrinology, 2005)
OBJECTIVE: Multiple pituitary hormone deficiency (MPHD) may result from defects of transcription factors that govern early pituitary development. We aimed to establish the prevalence of HESX1, PROP1, and POU1F1 gene defects in a population-based cohort of patients with MPHD and to analyse the phenotype of affected individuals. DESIGN AND METHODS: Genomic analysis was carried out on 74 children and adults with MPHD from the Czech Republic (including four sibling pairs). Phenotypic data were collected from medical records and referring physicians. RESULTS: One patient carried a heterozygous mutation of POU1F1 (71C > T), and 18 patients (including three sibling pairs) had a PROP1 mutation (genotypes 150delA/301delGA/9/, 301delGA/301-delGA/8/, or 301delGA/349T > A/1/). A detailed longitudinal phenotypic analysis was performed for patients with PROP1 mutations (n = 17). The mean ( +/-s.d.) birth length SDS of these patients (0.12 +/- 0.76) was lower than expected based on their mean ( +/-s.d.) birth weight SDS (0.63 +/- 1.27; P = 0.01). Parental heights were normal. The patients' mean ( +/-s.d.) height SDS declined to -1.5 +/- 0.9, -3.6 +/- 1.3 and -4.1 +/- 1.2 at 1.5, 3 and 5 years of age, respectively. GH therapy, initiated at 6.8 +/- 3.2 years of age (mean dose: 0.022 mg/kg per day), led to substantial growth acceleration in all patients. Mean adult height (n = 7) was normal when adjusted for mid-parental height. ACTH deficiency developed in two out of seven young adult patients. CONCLUSIONS: PROP1 defects are a prevalent cause of MPHD. We suggest that testing for PROP1 mutations in patients with MPHD might become standard practice in order to predict risk of additional pituitary hormone deficiencies.
Keywords: transkripční faktor Pit-1; Transcription Factor Pit-1; DNA-Binding Proteins; Humans; hypofyzární hormony; Longitudinal Studies; Pituitary Diseases; DNA vazebné proteiny; dítě; Sequence Analysis, DNA; kohortové studie; Transcription Factors; Child; tělesná výška; Female; mutace; nemoci hypofýzy; dospělí; Aged; Phenotype; senioři; lidé; Homeodomain Proteins; Pituitary Hormones; Cohort Studies; DNA; sekvenční analýza DNA; Adult; ženské pohlaví; longitudinální studie; Male; Body Height; Retrospective Studies; fenotyp; Adolescent; homeodoménové proteiny; polymerázová řetězová reakce; Polymerase Chain Reaction; retrospektivní studie; transkripční faktory; Mutation; mužské pohlaví; mladiství